2011
DOI: 10.4049/jimmunol.1102048
|View full text |Cite
|
Sign up to set email alerts
|

IL-1α and IL-1β Recruit Different Myeloid Cells and Promote Different Stages of Sterile Inflammation

Abstract: The immune system has evolved to protect the host from invading pathogens and to maintain tissue homeostasis. Although the inflammatory process involving pathogens is well documented, the intrinsic compounds that initiate sterile inflammation and how its progression is mediated are still not clear. Because tissue injury is usually associated with ischemia and the accompanied hypoxia, the microenvironment of various pathologies involves anaerobic metabolites and products of necrotic cells. In the current study,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

16
378
0
15

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 478 publications
(409 citation statements)
references
References 51 publications
(63 reference statements)
16
378
0
15
Order By: Relevance
“…The most notable changes in the cells treated with the combination of LG268 and LPS compared with LPS alone were a 3-fold downregulation of CSF3 and a 2.5-fold decrease of CXCL2 and IL1b mRNA expression. These cytokines play important roles in inflammation: CSF3 in the production and function of granulocytes (30), CXCL2 in the recruitment of neutrophils (31), and IL1b in promoting the infiltration of inflammatory myeloid cells and in angiogenesis (32,33). A complete list of the inflammatory cytokines, chemokines, and their receptors that showed any detectable changes in the panel of 440 genes following treatment with LG268 are listed in Supplementary Table S1.…”
Section: Resultsmentioning
confidence: 99%
“…The most notable changes in the cells treated with the combination of LG268 and LPS compared with LPS alone were a 3-fold downregulation of CSF3 and a 2.5-fold decrease of CXCL2 and IL1b mRNA expression. These cytokines play important roles in inflammation: CSF3 in the production and function of granulocytes (30), CXCL2 in the recruitment of neutrophils (31), and IL1b in promoting the infiltration of inflammatory myeloid cells and in angiogenesis (32,33). A complete list of the inflammatory cytokines, chemokines, and their receptors that showed any detectable changes in the panel of 440 genes following treatment with LG268 are listed in Supplementary Table S1.…”
Section: Resultsmentioning
confidence: 99%
“…IL-1α and IL-1β can function through the same IL-1 receptor. However, they may play different roles by recruiting different myeloid cells during different stages of sterile inflammation [42]. Inflammasomes and caspase-1 activity are required for the maturation and secretion of IL-1β.…”
Section: Discussionmentioning
confidence: 99%
“…IL-1α is present in the nucleus, cytosol, or cell membrane, and can be released from the necrotic cells to induce inflammation [41,42]. IL-1α and IL-1β can function through the same IL-1 receptor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further analyses revealed that IL-33 is constitutively expressed to high levels in the nuclei of endothelial and epithelial cells in vivo (27) and that it can be released in the extracellular space after cellular damage (23,24). IL-33 was, thus, proposed (23,24,27) to function as an endogenous danger signal or alarmin, similar to IL-1α and high-mobility group box 1 protein (HMGB1) (28)(29)(30)(31)(32), to alert cells of the innate immune system of tissue damage during trauma or infection.…”
mentioning
confidence: 99%